EVALUASI KELENGKAPAN DOKUMENTASI ASUHAN KEPERAWATAN DI KAMAR BAYI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Yun Martono (PSIK 11 UMY, 2011)
Documentation of nursing care is something that absolutely must be implemented for nurses to nursing professionalism. Documentation is the most important element in nursing care because through a complete and accurate documentation to member facilities for nurses in solving client problem This study of the title is Evaluation of completeness of Documentation Nursing Care Baby's Room in PKU Muhammadiyah Yogyakarta which aims to obtain real picture about the documentation of nursing care which in